Analisis Kampanye Perilaku Hidup Bersih dan Sehat (PHBS) untuk Pencegahan Penularan COVID-19 oleh Perguruan Tinggi di Malang Raya - Megasari Noer Fatanti; R. Zainal Fatah; Choiria Aggraini (Jurnal Nomosleca, 2021)
The COVID-19 pandemic has caused a global health crisis, include Indonesia, as a impacted country. The effort to citizens is by learning from home. One of the activities affected is that lectures carried out online, but allowed strict health protocols. To support this policy, several universities in Malang City have issued policies both through official appeals and creative content on the university's official social media (Instagram). This study aims to analyze how the Clean and Healthy Lifestyle (PHBS) campaign practices are carried out by universities in Malang City to prevent the transmission of the COVID-19 virus. This research was conducted in qualitative and data will analyze descriptively. Data collection was collected by digital archive on Instagram accounts of several campuses in Malang City. The results of this study indicate that (1) the campaign by universities related to COVID-19 has not been massive and has not been evaluated properly; (2) message content on social media still contains general information related to COVID-19, it is not specifically; (3) the intensity of the PHBS campaign through social media has decreased since 2021. The conclusion is health campaigns related to COVID-19 must continue to be carried out by all universities in Malang City for resilience in facing the COVID-19 pandemic. Keywords: COVID-19, Health Communication Campaign, PHBS, Social Media